1980
DOI: 10.1111/j.1365-2125.1980.tb05844.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and cardiovascular side effects of the beta 2‐adrenoceptor agonists salbutamol and rimiterol.

Abstract: The metabolic and cardiovascular side‐effects of intravenous infusions of therapeutic doses of beta 2‐adrenoceptor agonists salbutamol and rimiterol have been determined in four healthy male subjects. There were dose‐related increases in plasma glucose, renin activity, serum insulin and heart rate, and significant hyperlactataemia and ketonaemia. There were dose‐related decreases in plasma potassium, phosphate and corticosteroids and significant hypocalcaemia and hypomagnesaemia. The effects of equivalent mola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
43
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 35 publications
2
43
1
Order By: Relevance
“…There are a small number of reports of elevated lactate levels with intravenous salbutamol [1,2], with intravenous and nebulised salbutamol combined [3,4], and with inhaled salbutamol alone [5,6]. We were unable to find evidence of why only some patients develop hyperlactaemia, or the specific dose of salbutamol required to produce this unusual phenomenon.…”
contrasting
confidence: 44%
See 2 more Smart Citations
“…There are a small number of reports of elevated lactate levels with intravenous salbutamol [1,2], with intravenous and nebulised salbutamol combined [3,4], and with inhaled salbutamol alone [5,6]. We were unable to find evidence of why only some patients develop hyperlactaemia, or the specific dose of salbutamol required to produce this unusual phenomenon.…”
contrasting
confidence: 44%
“…We were unable to find evidence of why only some patients develop hyperlactaemia, or the specific dose of salbutamol required to produce this unusual phenomenon. Both Massara and colleagues [1] and Phillips and colleagues [2] used 'therapeutic' infusions of intravenous salbutamol and observed a rise in lactate levels. Rodrigo and Rodrigo studied 18 patients with acute severe asthma [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present studies both H-I 42 and atenolol competitively blocked an isoprenaline tachycardia with the effect of 400 mg H-I 42 being less than atenolol. The isoprenaline induced increase in blood glucose, serum insulin, serum potassium (Leitch etal., 1976) and serum lactate (Phillips et al, 1980) are all 02-adrenoceptor mediated responses. There was no difference in the change of these metabolic parameters after any of the treatments.…”
Section: Discussionmentioning
confidence: 94%
“…Salbutamol has been shown to increase supine heart rate in previous studies (Leitch et al, 1976;Philips et al, 1980;Kennedy & Simpson, 1969) and the specific 32-adrenoceptor antagonist, ICI 118,551 (Bilski et al, 1983) has been shown to abolish this increase in heart rate (McCaffrey et al, 1986) indicating that it is mediated by the 12-adrenoceptor. However the mechanism of the rise in heart rate is unclear and may be partly reflex, secondary to peripheral vasodilation or due to direct stimulation of P2-adrenoceptors in the heart (Stiles et al, 1983) or stimulation of presynaptic 132-adrenoceptors facilitating noradrenaline release at the sympathetic nerve endings (Stjarne & Brundin, 1976).…”
Section: Discussionmentioning
confidence: 99%